ANALISIS FAKTOR GANGGUAN BERBAHASA LATAH PADA PENUTUR BAHASA WANITA DEWASA - Ray, Sukma Adelina; Wulandari, Wina (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
Latah is a language disorder that we often encounter in the midst of society and is generally suffered by women by imitating someone's words or actions that are carried out by sufferers spontaneously or suddenly. Talkative behavior is a unique and interesting behavior to be discussed and studied in depth due to the fact that this type of language disorder is often found in the surrounding environment and has even become entertainment for people who like to surprise talkative sufferers. So that the goal in this discussion is to determine and describe speech types of talkative speech sourced from data sources and the factors that cause sufferers to experience speech disorders. This research used a descriptive qualitative research type and the data obtained was obtained or sourced from the speech of the research informant (subject). The locations in this study were Jalan Benteng Hilir, Medan Tembung District and Jalan Gurilla, Medan Perjuangan District, Medan City. The listening method, note-taking technique, and recording technique are ways to obtain data from sources which are then analyzed. The results of the study can be concluded that the language disorder experienced by subject I was talkative, while subject 2 experienced speech talk, echolalia, koprolalia, Automatic obedience and the causal factor was due to conditioning (environmental factors) which influenced them to experience speech talk.